Modeling Perceived Quality, Customer Satisfaction and Probability of Guest Returning to the Destination - Olivera Blagojevic Popovic; Vinko Nikic; Iva Bulatovic; Milica Delibasic (Montenegrin Journal of Economics, 2018)
In the hotel industry, it is a well-known fact that, despite of quality and variety of services provided, there is a low probability that the guests will return. This research is focused on identifying the basic factors of the hotel offer, which could determine the influence on the correlation between the guests’ satisfaction and the probability of their return. The objective of the article is to explore the relationship between the guests’ satisfaction with the quality hotel services in total (including the tourist offer of the place) and the probability of his return to the same destination. The questionnaire method was applied in the survey, and the data were analysed based on factor analysis. Thereafter, the model for forecasting the probability of the guests returning to the destination was established, by using the example of Montenegrin tourism. The model represents a defined framework for the guest’s decision-making process. It identifies two main characteristics of guest experiences: satisfaction and rated quality (of the destination’s overall hotel service and tourist offer). The same model evaluates the impact of the above factors on the probability of the guests’ returning to the same destination. The starting hypothesis was the existence of a high degree of correlation between the guests’ satisfaction (with the destination’s hotel services and tourist offer) and the probability of returning to the selected Montenegrin destinations. The research confirmed the above-mentioned hypothesis. The results have revealed that there are significant differences in perceived quality, i.e. satisfaction between the target groups of Eastern and Western European tourists